Physicochemical quality improvement of ready cook baby corns using calcium propionate immersion - Promyou, S.; Chimsonthorn, V.; Kijka, C.; Supapvanich, S. (My University, 2020)
The effect of calcium propionate (Ca-propionate) on physicochemical quality changes of ready cook baby corn (Zea mays L.) during storage was investigated. It was found that Ca-propionate treatment retarded the loss of texture which was concomitant with the lower EDTA-soluble pectin and higher Na2CO3 soluble pectin concentrations compared to untreated baby corns. Ca-propionate treatment did not obviously affect total sugars content, antioxidant activity and free radical scavenging activity compared to untreated samples. However, Ca-propionate treatment induced bioactive compounds such as total phenols, flavonoids and ascorbic acid contents of ready cook baby corns during storage. Therefore, Ca-propionate immersion is an alternative improving quality especially texture and nutritional values of ready cook baby corns during cold storage.
Keywords: Baby corn; Calcium propionate; Nutritional value; Texture